Innovation practices in small technology-based companies during incubation and post-incubation periods - Oliveira, Pedro Henrique de; Fernandes Terence, Ana Claudia [UNESP] (Emerald Group Publishing Ltd, 2018)
Purpose - innovation is a constant attribute in the management processes of technology-based companies (TBCs), mostly small and young, and plays a relevant role in their competitiveness and survival. However, the authors assumed that the characteristics of innovation practices differ between incubated and post-incubated companies, in such aspects as formality, type, posture and strategy. The purpose of this paper is to report the innovation practices identified in small TBCs in the incubation and post-incubation periods (graduate companies). Design/methodology/approach - To achieve the purpose, the authors carried out a multiple case study with four TBCs, two incubated and two post-incubated (graduate); the study was qualitative and exploratory, and the authors collected data with their managers. Findings - The results show that these companies have high levels of innovation, which is a determinant factor for their presence in the business market they create technological innovations in products and services, mostly incremental, such as improvements in existing products or reduction of internal costs of manufacturing. In addition, the results also show important features of the innovations, such as the interaction with other incubated companies and with universities and research centers. Originality/value - The authors conclude that there were changes in innovation practices, in the transition from incubated to graduate companies, such as the formalization of process, a shift in focus toward the customer and an increase in resources and in projects' relevance.
Keywords: Innovation; incubation; Small firm; Technology-based company; Post-incubation